Fluoride effect on the process of alveolar bone repair in rats: evaluation of activity of MMP-2 and 9 - Mileni da Silva Fernandes; Gisele Miyamura Martins; Lucas Makoto Shimoraha; Flávia Godoy Iano; Marcela Mitsuko Yanai; Tânia Mary Cestari; Marília Afonso Rabelo Buzalaf; Rodrigo Cardoso de Oliveira (Revista Sul-Brasileira de Odontologia, 2013)
The aim of this study was to evaluate comparatively the effect of fluoride (F) on the activity of matrix metalloproteinases 2 and 9 (MMP-2 and MMP-9) involved in process of alveolar bone repair. Material and methods: This study used 4 groups of Wistar rats with 80 days of life (n = 160) which received drinking water containing different doses of fluoride (NaF): 5, 15, 50 ppm and deionized water (control) throughout the experiment. These animals had their right upper incisors extracted. After extraction, the animals were euthanized at 7, 14, 21 and 30 days and the hemi-maxillae were collected for microscopic analysis (Hematoxylin and Eosin and immunohistochemistry for MMP-9) and zymography (MMP-2 and 9). Results: Microscopically the process of bone repair was similar in all groups, being noted only a delay of the blood clot resorption and bone formation in the group of 50 ppm F. The expression for MMP-9 showed differences between groups only during the initial repair (7 days). However, the zymography showed no significant differences between treated and control groups. Conclusion: Ours results suggest an effect of fluoride on the activity of MMPs 2 and 9 at the initial period of alveolar repair which could be associated to the process of blood clot remission and delay in bone repair. Further studies are needed to establish the relationship between the initial process of resorption of the blood clot, and the involvement of MMPs 2 and 9 and its regulators/tissue inhibitors.